Perilaku Sosial Peserta Didik dalam Budaya Etika Sopan Santun pada Guru di SD Negeri Baturejo 03 - Putri Meilani, Riska; Prichilia Hasintha Lofha; Vindy Audina Adelia; Nur Fajrie; Sekar Dwi Ardiyanti (Universitas Palangka Raya, 2023)
One aspect that must be instilled in students is social behavior. Social behavior is a form of character that must exist in every student. This certainly cannot escape the role of the world of education. This article aims to analyze the social behavior of students in a culture of polite ethics in elementary school teachers. This article uses a qualitative approach research method with 4 data collection techniques, namely interviews, observation, documentation and interview transcripts. The courtesy ethics of the students of SD N Baturejo 3 toward teachers is low because there are still many students who behave impolitely towards their teachers, both in impolite words and actions. This is influenced by environmental factors such as the influence of friends and the playing environment and the rapid development of technology in the globalization era. In addition to the ethical courtesy of students towards teachers, some students also have not shown politeness towards peers, for example calling friends by their parents' names.